PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERDASARKAN STRATEGI PQ4R (PREVIEW, QUESTION, READ, REFLECT, RECITE, REVIEW) DENGAN TEKNIK MIND MAPPING PADA SUB POKOK BAHASAN HIMPUNAN KELAS VII - Nurhidayati, Laily Anisa; Susanto, S; Dafik, D (Kadikma, 2014)
Abstract. Strategy of PQ4R (Preview, Question, Read, Reflect, Recite, Review) with the technique of Mind Mapping is the learning to create combination and relation between new information that have been know with the use of all in the students’ brain and write about what they learn in a piece of paper. This research is expected to know the process and result of the development of mathematics learning instruments based on strategy of PQ4R with the technique of Mind Mapping in sub subject of set for class VII. Learning instruments development model refers to Thiagarajan, Semmel and Semmel Model (4-D) Model. The result product is lesson plan, student books, work sheets, and evaluation test. Based on validation process and tryout the learning sets can be concluded that the learnig sets had been appropriate with validate, practice, and effective criteria. Key Words : PQ4R, Mind Mapping, Set, 4-D Model